Clinical Outcome of Intravenous Glucocorticoid and Rituximab in Moderate to Severe Thyroid Eye Disease - Salmarezka Dewiputri; M Sidik (Majalah Oftalmologi Indonesia, 2016)
Background: Thyroid eye disease (TED) is the most common extrathyroidal manifestation of Graves’disease, also a serious and potentially sight-threatening. Current treatment method by using glucocorticoidis still unclear. Rituximab is a biological agent that has been used successfully. In the literatures, thepotential drug use for TED has been discussed but there is no guidelines published outliningrecommendations. The objective of this literature review is to evaluate the efficacy and safety ofglucocorticoid and rituximab for the treat-ment of TED in terms of clinical outcome, side effect, andrelapse rate.Methods: The literature search was conducted from Google Scholar, MEDLINE database using Pubmedfor journal articles that were published and related to the use of intravenous glucocorticoid andimmunobiologic therapy in Graves’ ophthalmopathy.Results: A total of 10 articles were reviewed in this paper. Six studies evaluated IVGC treatment, 3studies evaluated rituximab treatment, 1 study evaluated and compared IVGC and rituximab treatment.Most of the reviewed studies reported improvement on proptosis, while some studies reportedimprovement in proptosis by using rituximab.Conclusion: Rituximab is as effective as IVGC in decreasing proptosis. Rituximab was significantlybetter and earlier that IVGC in reducing CAS.Keywords: intravenous glucocorticoid, rituximab, thyroid eye disease